Pengaruh Konflik Kerja Dan Beban Kerja Terhadap Kinerja Pegawai Pada Kantor Pertanahan Kabupaten Sikka - Wiliborda Da Iga; Imanuel Wellem; Maria Modesta Missi Mone (Jurnal Projemen UNIPA, 2026)
This study aims to: (1) describe Employee Performance, Work Conflict, and Workload; and (2) analyze the effect of Work Conflict and Workload on Employee Performance, both partially and simultaneously. The population of this study consisted of 47 employees of the Land Office of Sikka Regency. Since the population was relatively small, a census (total sampling) technique was employed. Data were collected through questionnaires and analyzed using descriptive statistics and inferential statistics, specifically multiple linear regression analysis. Hypothesis testing was conducted using the F-test and t-test. The results of the descriptive analysis indicate that the Employee Performance variable falls into the good category, the Work Conflict variable is also in the good category, and the Workload variable is likewise categorized as good. The results of the t-test show that, partially, Work Conflict has a negative and insignificant effect on Employee Performance. Likewise, Workload has a negative and insignificant effect on Employee Performance. Meanwhile, the results of the F-test indicate that Work Conflict and Workload simultaneously have a significant effect on Employee Performance. The coefficient of determination analysis shows that the two independent variables in this study explain 20.9% of the variation in Employee Performance at the Land Office of Sikka Regency, while the remaining 79.1% is explained by other variables not included in this study. Keywords: Work Conflict, Workload, Employee Performance